Identifikasi tungau hama pada tanaman pepaya di Pulau Lombok - Wieke Mei Dina; Sugeng Santoso (Perhimpunan Entomologi Indonesia, 2017)
Lombok Island (West Nusa Tenggara) is one of the major papaya producer in Indonesia. In the last five years, papaya production in West Nusa Tenggara has decrease continuosly. Pest mites is one the constraint found in papaya production in Indonesia. At the present there is no data available related with mites on papaya in Lombok island. Thus, the aim of the research is to determine the identity of pest mites on papaya in Lombok Island. Mites collected from 50 different location of 5 districts in Lombok Island. From each location, 3 plant were sampled for observation, two leaves from each plants were collected. Identification of mites were conducted by using morphological characters such as stigma, gnathosoma, and idiosoma. The results revealed twelve spesies of pest mites of papaya in Lombok island, they were Aculops pelekassi Keifer, Calacarus carinatus Keifer, Brevipalpus californicus Banks, B. obovatus Dannadieu, B. phoenicis Geijskes, Tenuipalpus pasificus Baker, Eutetranychus africanus Tucker, Panonychus citri McGregor, Tetranychus fijiensis Hirst , T. kanzawai Kishida, T. piercei McGregor, and Tarsonemus bilobatus Suski.